Parents' or Guardians' Knowledge, Attitudes and Practices in the Prevention and Management of Childhood Myopia - Yifeng Qian; Peirong Lu (Ophthalmology and Therapy)
Abstract Introduction The aim of this study was to assess the knowledge, attitude, and practices (KAP) of parents or guardians regarding the prevention and management of childhood myopia. Methods This cross-sectional study was conducted at the Department of Ophthalmology in the First Affiliated Hospital of Soochow University (Suzhou, China) between August 2023 and November 2023. Parents or guardians who willingly volunteered to take part in the study were surveyed using a self-designed questionnaire. Results A total of 571 participants returned valid questionnaires, among whom 288 respondents (50.44%) fell within the 31- to 40-year age group and 474 respondents (83.01%) were identified as myopic. The mean KAP scores for the knowledge, attitude and practices dimensions were 23.34 ± 3.05 (possible range: 0–26), 46.47 ± 4.02 (possible range: 12–60), and 40.52 ± 7.07 (possible range: 11–54), respectively. Structural equation modeling analysis indicated that education had a direct effect on knowledge (estimate = 0.41, P = 0.038), while knowledge directly influenced both attitude (estimate = 0.40, P < 0.001) and practices (estimate = 0.36, P < 0.001). Also, attitude was found to have a direct impact on practices (estimate = 0.45, P < 0.001). Conclusions Parents or guardians had adequate knowledge, a positive attitude, and proactive practices towards the prevention and management of childhood myopia, which might be affected by their educational level. This comprehensive understanding of parental perspectives highlights the potential for targeted interventions in clinical settings to further enhance pediatric eye care.